Injury prevention and public health (Italian Journal of Public Health, 2010)
Injuries are one of the most under-recognized public health problems facing the world today. With more than 5 million deaths every year, violence and injuries account for 9% of global mortality, as many deaths as from HIV, Malaria and Tuberculosis combined. Eight of the 15 leading causes of death for people ages 15 to 29 years are injury-related: road traffic injuries, suicides, homicides, drowning, burns, war injuries, poisonings and falls. For every death due to war, there are three deaths due to homicide and five deaths due to suicide. However, most violence happens to people behind closed doors and results not in death, but often in years of physical and emotional suffering [1]. Injuries can be classified by intent: unintentional or intentional. Traffic injuries, fire-related injuries, falls, drowning, and poisonings are most often classified as unintentional injuries; injuries due to assault, selfinflicted violence such as suicide, and war are classified as intentional injuries, or violence. Worldwide, governments and public and private partners are increasingly aware of the strains that unintentional injuries and violence place on societies. In response they are strengthening data collection systems, improving services for victims and survivors, and increasing prevention efforts.